The Armorial Tombstone of Lady Jonet Ker at Restalrig, 1596 - Douglas, William (Proceedings of the Society of Antiquaries of Scotland, 1928)
The armorial tombstone, located at St Triduana's Well is of interest because of its inscription and heraldic shield, which combines the arms of Robert Logan and Ker. Robert Logan's right to arms was forfeited in 1609 because of his involvement in the Gowrie Conspiracy which was a plot to kidnap King James VI. AB